The Unequal State Intervention on the Territories in Latin America - Pradilla Cobos, Emilio; Márquez López, Lisett (Universidad del Rosario, 2022)
Part of a broader work on uneven territorial development in Latin America, this article makes a historical review of the cumulative and dynamic impacts on the territory, the cities in particular, of the policies and actions of the different state forms existing in the formations. socio-economic aspects of the region, from the conquest by the Iberian powers, to the present day when the consolidation of the neoliberal pattern of capital accumulation, as the current architecture of historical capitalism, determines the structure, form, processes and conflicts of our large metropolises and regional cities, dominated by transnationalized real estate–financial capitals, in their articulation with subsidiary governments and facilitators of their operation. It is an effort of theoretical construction based on the interpretation of the specific historical processes that occurred in a region that has shared similar situations of domination and subordination to the different hegemonic powers for centuries.